Green Entrepreneurship as a Mediator of Innovation and Environmental Orientation on the Sustainability of Coastal Fisheries MSMEs in Ambon City - Wendy Souisa; Cynthia Imelda Tjokro; Nurfatwa Andriani Yasin (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study aims to analyze the role of green entrepreneurship in mediating the influence of innovation and environmental orientation on the sustainability of coastal fisheries MSMEs in Ambon City. Research Design & Methods: The study used a quantitative approach with an explanatory design. Data were collected through a survey of 200 fisheries MSMEs selected using a stratified purposive sampling method. The research model was tested using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze the direct and indirect relationships between variables. Findings: The results showed that innovation did not have a significant direct effect on the sustainability of fisheries MSMEs, but had a positive and significant effect on green entrepreneurship. Environmental orientation has a significant effect on MSME sustainability and green entrepreneurship. Furthermore, green entrepreneurship significantly mediates the relationship between innovation and environmental orientation on MSME sustainability. Environmental orientation was proven to have a significant effect on the sustainability of MSMEs and green entrepreneurship. Implications & Recommendations: The sustainability of fisheries MSMEs is not achieved through innovation alone, but requires strengthening green entrepreneurship as a strategic approach. Strengthening green innovation capacity through government policy support, increasing environmental literacy and green entrepreneurship, expanding access to environmentally friendly technology, and developing mentoring and incentives to encourage the integration of innovation and environmental orientation in sustainable fisheries MSME business strategies. Contribution & Value Added: Strengthening the perspective of sustainable entrepreneurship by positioning green entrepreneurship as a strategic mechanism that bridges innovation and environmental orientation in improving the sustainability of MSMEs.